Chemical and Spectroscopic Characteristics of Anthrosol (Amazonian Dark Earth) and Surrounding Soil from the Brazilian Amazon Forest: Evaluation of Mineral and Organic Matter Content by Depth - Bento, Lucas R. [UNESP]; Constantino, Isabela C. [UNESP]; Tadini, Amanda M.; Melo, Camila A. [UNESP]; Ferreira, Odair P.; Moreira, Altair B. [UNESP]; Bisinoti, Marcia C. [UNESP] (Soc Brasileira Quimica, 2020)
The chemical and spectroscopic characteristics of soil organic matter (SOM) isolated from Amazonian dark earth (ADE) and surrounding soil (SR) were evaluated according to the soil depth. The results showed opposite trends for the soils. While ADE featured SOM with a greater aromatic condensation degree and greater hydrophobicity in the top layer, the SR showed more aliphatic and polar SOM. The SOM arrangement from ADE was less hydrophobic, aromatic, and more polar in depth. In contrast, the SOM from SR showed an increase in molecular weight and hydrophobicity. Besides the aromatic protection in the SOM from ADE, there was organo-mineral protection through binding to soil minerals. This suggested that the SOM from ADE was protected by its hydrophobicity and interaction with minerals compared with that from the SR, thereby showing that the combination of both characteristics is important to create new technologies for soil carbon storage.
Keywords: Terra Preta de Indio; organo-mineral interaction; soil organic matter; iron; aluminum